The Influence of Principal's Instructional Leadership and Work Motivation on Teachers' Professional Competence - Lela Iman Ningrum; Widya Kusumaningsih; Soedjono (Jurnal Educative: Journal of Educational Studies, 2025)
The report card is an official document that records the development of students' learning outcomes over a certain period. The achievement of the report card for public elementary schools in Ulujami District shows a lower percentage compared to the average achievement of the quality of learning in public elementary schools in Pemalang Regency. The low quality of learning in public elementary schools in Ulujami District is also a result of the low professional competence of teachers. Therefore, an increase in teachers' professional competency is needed to improve the quality of learning. This study aims to analyze the effect of the instructional leadership of the school principal and work motivation on the professional competency of teachers in public elementary schools in Ulujami District, Pemalang Regency. The research uses a quantitative approach, with data collected through standardized questionnaires from 178 teachers in Ulujami District's public elementary schools. The results of the multiple regression analysis indicate that the instructional leadership of the school principal and work motivation both have a positive and significant effect on the professional competence of teachers. These findings emphasize the importance of strengthening instructional leadership and teacher work motivation in efforts to improve the professional competence of teachers. The practical implications of this research can serve as a reference for school management and policymakers in designing teacher quality improvement programs and open opportunities for further research that can explore other factors influencing teacher professional competence.